Predictors of sports education: current trends - Masyagina N.V.; Leontyeva M.S.; Martynenko I.V.; Lyakh V.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to elucidation of the fundamental principles of the theory of physical culture and sports, with an eye to contemporary circumstances. Methods and structure of the study. The research was conducted at MSUSiT, where the content of scientific and educational publications was examined. Results and conclusions. The fundamental principles of sports science are enriched by the findings of contemporary research. The definitions of sports and physical culture are clarified, and a distinctive framework for the structure of the field of physical culture and sports is presented. The position of sports theory within the scientific framework is established, and a diverse array of sports is identified. The multifaceted roles of physical culture are explored, and the interconnections between the constituent parts of the field of physical culture and sports are elucidated.